Age diversity and innovation: Do mixed teams of "old and experienced" and "young and restless" employees foster companies' innovativeness? - Andrea Hammermann; Matthias Niendorf; Jörg Schmidt (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
In Germany, the labour force is ageing rapidly. At the same time, age heterogeneity within companies is rising. The literature on diversity argues that heterogeneity can have a positive as well as a detrimental effect on team outputs. Our paper sheds light on the impact of age diversity on the likelihood of a company to create product or process innovations. Based on our analysis of the Linked Employer-Employee-Data from the Institute for Employment Research (IAB) over the 2009-2013 period, we focus on different indicators of age diversity within a company's workforce (variety, separation and disparity). We find that a rise in the average age of a company's workforce has a negative impact on innovation, but age diversity measured by the standard deviation of age or the average age gap increases the probability of a company to create innovations. In addition, the uniformity of the age distribution does not affect innovativeness. Different results for age and tenure diversity suggest a higher importance of generalised human capital for creativity processes compared to company-specific knowledge gained during employment within a company. – – Die Erwerbsbevölkerung in Deutschland altert rasant, gleichzeitig nimmt aber auch die Altersheterogenität in den Belegschaften zu. In der Literatur finden sich sowohl Hinweise auf einen positiven wie auch einen negativen Einfluss der Altersheterogenität auf den Teamerfolg. Die vorliegende Studie untersucht, inwieweit die Altersheterogenität die Wahrscheinlichkeit eines Betriebs beeinflusst, Produkt- oder Verfahrensinnovationen hervorzubringen. Auf Basis von Linked Employer-Employee-Daten des Instituts für Arbeitsmarkt- und Berufsforschung (IAB) der Jahre 2009 bis 2013 werden verschiedene Indikatoren zur Messung der Altersheterogenität in der Belegschaft verwendet (Varietät, Separation, Disparität). Im Ergebnis findet sich ein negativer Effekt des Durchschnittsalters auf die Innovationsfähigkeit, allerdings erhöhen die Standardabweichung des Alters und die durchschnittliche Alterslücke die Wahrscheinlichkeit eines Betriebs, Innovationen hervorzubringen. Eine Gleichverteilung der Altersstruktur zeigt hingegen keinen Zusammenhang zur betrieblichen Innovationsfähigkeit. Die unterschiedlichen Ergebnisse zur Heterogenität des Alters und der Betriebszugehörigkeitsdauer weisen zudem auf eine höhere Bedeutung des allgemeinen Humankapitals für kreative Prozesse hin - im Vergleich zum Humankapital, welches betriebsspezifisch erworben wird.
Keywords: J14; J24; M14; 330; Age Diversity; Company Innovativeness; Linked Employee-Employer-Data